Implementation of Faraidh's Provisions in Hibah Wasiat (A Case in South Banjar Kalimantan) - Wahidah, Wahidah; Azhar, Alias (Universitas Islam Negeri Raden Intan Lampung, 2019)
This research illustrates the practice of inheritance in the Banjar community of South Kalimantan. The aim is to see the extent to which the provisions of Islamic inheritance law (farāidh) are applied by the member of society in everyday life. This phenomenon is revealed through several field research methods, especially in-depth interviews, the results of which are then analyzed to obtain conclusions. This study found the fact that although in general, the majority of Banjar people of South Kalimantan resolved their inheritance cases by farāidh (Islamic inheritance law), there was a tendency for some citizens to put forward the spirit of